Risk assessment for integration of unmanned aerial vehicles (UAVs) to aerodromes - Radhakrishnan Keerthana (Nanyang Technological University, 2020)
Unmanned Aerial Vehicles are a fast-paced, emerging technology, and day-by-day they are becoming more actively engaged in our everyday activities. As the applications of UAVs are spread over a vast expense, the research intends to make use of its full potential in the future by integrating it into an opportune area of development, the aerodromes. Despite that, being a country’s critical infrastructure, aerodromes are currently becoming a target to create an asymmetric threat to people with UAVs, as this kind of breach is easy and cheap. The foremost concern of this research is to understand the safety issues and its vulnerability when UAVs are united to the aerodrome environment. The unification poses threats to aircrafts, infrastructure, and the people around. The research tries to comprehend the issue through a risk assessment process. With the help of different phases of the assessment and various methodologies, the threats posed by the UAVs, the probability of a collision to happen, and the severity of the end-effects of a crash are all determined. To perceive the variation in risks produced by distinct UAVs, three different UAVs are put through thorough analysis. The evaluated collision risks values are then compared against a high level target safety criteria that would result in safe operation. The compared results revealed that most of the small UAVs (<4kgs) would produce equivalent risks to the aerodrome surroundings. The results also demonstrated that the risks put on aircraft traffic and human traffic are high with a likelihood of collision occurrence in the order of 10-2 collisions per hour of UAV flight and also results in a hazardous or catastrophic event. Whereas the damage to structures is less intense in the order of 10-3 collisions per hour and can be tolerated without significant loss. However, it is difficult to find locations or applications without involving aircrafts and people. It is concluded that integrating UAVs to aerodromes may wind up as a disastrous event and hence it is unsafe to execute the operation in present circumstances. Incase of UAV intrusions into an airport, based on the position of UAV, the risks at that location can be evaluated and corresponding further actions can be performed. In the future, after the implementation of adequate mitigation measures decreasing the risk-level to acceptable terms, successful, secure integration of UAVs can be executed in the aerodromes.